Parental ADHD in pregnancy and the postpartum period – A systematic review. (May 2021) - Kittel-Schneider, Sarah; Quednow, Boris B.; Leutritz, Anna Linda; McNeill, Rhiannon V.; Reif, Andreas
Highlights: Female ADHD is associated with the risk of teenage pregnancies. Maternal ADHD is associated with an increased risk of pre-eclampsia, infection and caesarean section. Maternal ADHD is associated with negative birth outcomes. ADHD medication seem not to be major teratogens. There are no severe acute complications associated with methylphenidate during breastfeeding. Abstract: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders worldwide, and in the majority of patients persists into adulthood. However, it remains unclear how maternal ADHD could affect pregnancy and birth as well as early mother-(father)-child interaction. There are several studies investigating the effect of depressed or anxious parents on parent-child-interactions in early infancy, but data about the influence of parental ADHD is lacking although it is a common mental disorder in parents. Additionally, the prescription of stimulant and other ADHD medication for adult ADHD patients is rising due to improved diagnostic procedures and a greater awareness of this disorder in adulthood among psychiatrists and psychologists. However, this leads to increased numbers of treated ADHD women that wish to have children or experience unplanned pregnancies while taking stimulant medication. In our systematic review we aimed at analysing the current evidence for the association of maternal ADHD with pregnancy and birth outcomes, pregnancy risks and health behaviour in pregnancy, as well as the association of parental ADHD with early parent-child interaction and early child development in the first 3 years. Furthermore, we reviewed recent evidence on the risks of stimulant and non-stimulant treatment for ADHD in pregnancy and lactation.